The role of repetition as a stylistic tool in political texts (Zien Journal of Social Sciences and Humanities, 2022)
The purpose of this study is to do a research into the importance and specific functions of repetition as a stylistic device in political texts while representing strategy by politicians. The comparison which was drawn for this study is based on the speeches of a famous politician Martin Luther king, Winston Churchill and a former president of the USA, Donald Trump. This study concentrates on highlighting the impact of stressing on the same word repetitively by above-mentioned politicians to defy their stance during their speeches so as to convince the audience which often requires to exploit words to convey an implicit message and to manipulate the folks by provoking their political agenda to keep the authority